A putative terpene cyclase gene (CcPtc1) is required for fungal development and virulence in Cytospora chrysosperma - Yang, Yuchen; Yu, Lu; Qiu, Xiaolin; Xiong, Dianguang; Tian, Chengming (Frontiers in Microbiology, 2023)
Cytospora chrysosperma is a destructive plant pathogenic fungus, which causes canker disease on numerous woody plants. However, knowledge concerning the interaction between C. chrysosperma and its host remains limited. Secondary metabolites produced by phytopathogens often play important roles in their virulence. Terpene cyclases (TC), polyketide synthases (PKS) and non-ribosomal peptide synthetases (NRPS) are the key components for the synthesis of secondary metabolites. Here, we characterized the functions of a putative terpene type secondary metabolite biosynthetic core gene CcPtc1 in C. chrysosperma, which was significantly up-regulated in the early stages of infection. Importantly, deletion of CcPtc1 greatly reduced fungal virulence to the poplar twigs and they also showed significantly reduced fungal growth and conidiation compared with the wild-type (WT) strain. Furthermore, toxicity test of the crude extraction from each strain showed that the toxicity of crude extraction secreted by ΔCcPtc1 were strongly compromised in comparison with the WT strain. Subsequently, the untargeted metabolomics analyses between ΔCcPtc1 mutant and WT strain were conducted, which revealed 193 significantly different abundant metabolites (DAMs) inΔCcPtc1 mutant compared to the WT strain, including 90 significantly downregulated metabolites and 103 significantly up-regulated metabolites, respectively. Among them, four key metabolic pathways that reported to be important for fungal virulence were enriched, including pantothenate and coenzyme A (CoA) biosynthesis. Moreover, we also detected significant alterations in a series of terpenoids, among which (+)-ar-turmerone, pulegone, ethyl chrysanthemumate, and genipin were significantly down-regulated, while cuminaldehyde and (±)-abscisic acid were significantly up-regulated. In conclusion, our results demonstrated that CcPtc1 acts as a virulence-related secondary metabolism factor and provides new insights into the pathogenesis of C. chrysosperma.